Effects of a human resource management model on job performance: an empirical study in Peruvian educational management - Delgado Vela, Ingrid Karina (2025)
Context: Human resources management is a fundamental element for strengthening work performance in public educational institutions. The purpose of this study was to analyze the effects of a human resource management model on work performance in the Peruvian educational management. Methods: An applied study was implemented with a non-experimental design, cross-sectional and propositional descriptive approach. A total of 57 workers participated in the survey, which was conducted using a structured questionnaire to collect information on human resource management and job performance. Results: The findings revealed significant deficiencies in human resource management, specifically in personnel selection, induction processes, and a lack of stimuli, affecting team development and motivation. Likewise, the competencies required for senior positions are not adequately identified. Work performance demonstrated limited commitment and deficiencies in planning and responsibility, resulting in reduced efficiency and non-compliance with institutional objectives. Conclusions: The proposed human resource management model demonstrated its effectiveness in improving work performance, as supported by a validation of 96.30% which confirms its viability and applicability in similar public educational institutions.